Морфо-функциональный анализ мышц плеча летучих мышей в связи с их полетом - Ковтун, М.Ф. (Вестник зоологии, 1970)
As a result of investigations it was established that the structure, correlative development and topography of the shoulder muscles in eight species of Chiroptera are not similar and depend on the flying abilities of the animals. The above-mentioned facts apply, in the first turn, to the corracoid caput (caput brevis) of biceps. So, in quickly flying Chiroptera the coracoid caput exceeds the one (caput longus) in weight, whereas in slowly flying Chiroptera it is vice versa. The angle of crossing of long axes of coracoid and long caputs of biceps also is not similar. It is greater in quickly flying species.